Police Discretion in Traffic Criminal Cases Committed by Children - Sylvia Claudia Agustina; Heni Siswanto; Nikmah Rosidah (Faculty of Law, Universitas Lampung, 2020)
Traffic crimes committed by children generally occur because of negligence. The problem of this research is how the implementation of police discretion in traffic criminal cases committed by children and why there are obstacles in the implementation of police discretion in traffic criminal cases carried out by children. The problem approach in this study uses a normative juridical approach. Data collection is done by library research. Data were analyzed qualitatively to obtain research conclusions. The results showed that the implementation of police discretion in traffic criminal cases by children is a form of settlement of cases outside the court carried out with a peace process based on good faith between the parties involved in traffic accidents to pursue settlement in a family way. The settlement of a traffic accident case does not have to be a criminal punishment or the imposition of a criminal sanction, in this case based on the occurrence of an act, if it occurs due to negligence and error not on the suspect. Factors that impede the implementation of police discretion in traffic criminal cases committed by children are the limited number of members of the Metro Police Traffic Satlantas in handling traffic cases, incomplete data and information submitted by the perpetrators and victims involved in traffic criminal cases, so that the perpetrators and victims only provide data deemed not potentially detrimental to their party. Cultural Factors, namely the personal character of the offender, victim and his family who do not support the settlement of cases outside the court.